Tuning Ion Mobility and Molecular Confinement in High-Performance Polymer Electrolytes for Energy Storage - Yousef, Ezzeldien Yousef Muhammed (AUC Knowledge Fountain, 2026)
This research addresses the critical energy density limitations of aqueous supercapacitors, which are traditionally constrained by the narrow electrochemical stability window (ESW) of water 1.23 V. By employing two distinct molecular engineering strategies, this study developed high-performance electrolyte systems that significantly extend voltage stability and thermal resilience. The first system, CsBr@PAM/HA, utilizes a polyacrylamide and hyaluronic acid hydrogel matrix. This system exploits the chaotropic nature of Cs+ ions to disrupt the aqueous hydrogen-bonding network, enhancing ionic conductivity to 104 mS cm-1. Through systematic salt screening, CsBr was identified as the optimal electrolyte, enabling a stable 2.0 V operating window with a specific capacitance of 100 F g-1 and exceptional cycling stability over 10,000 cycles. The second system, LiBr@PQ-7, introduces a quasi-solid-state paradigm using a cationic polymer (Polyquaternium-7). The permanent quaternary ammonium groups in the matrix immobilize Br─ anions, suppressing parasitic oxidation and extending the ESW to 2.2 V. This device achieved an energy density of 61.74 Wh kg-1 and demonstrated remarkable climate resilience. Due to a high concentration of non-freezable bound water (73.7%), the electrolyte maintained performance at −15 °C and showed enhanced capacitance at temperatures up to 80 °C without polymer degradation. Together, these systems establish complementary design paradigms, cation mobility enhancement and anion immobilization, providing a comprehensive framework for engineering next-generation, high-voltage, and thermally robust supercapacitors for sustainable energy storage.